A N-self-doped carbon catalyst derived from pig blood for oxygen reduction with high activity and stability. (1st April 2015) - Zhang, Jian; Li, Qidong; Zhang, Chenyu; Mai, Liqiang; Pan, Mu; Mu, Shichun
Graphical abstract: Highlights: A novel non-noble metal catalyst for oxygen reduction is fabricated by carbonizing pig blood and adding trace iron. The catalytic activity of this catalyst very approaches that of the commercial Pt/C in alkaline media. This catalyst shows both superior stability and fuel tolerance than Pt/C in alkaline media. It gives a promising alternative to noble metal catalysts by means of such abundant natural biological materials. Abstract: A new pig blood-derived N-self-doped carbon catalyst is successfully fabricated with aid of metal iron in the synthetic process. The prepared catalyst shows an excellent oxygen reduction reaction (ORR) performance with high onset potential (Eonset = −0.04 V) and half-wave potential (E1/2 = −0.16 V), which very approaches that of the commercial Pt/C catalyst (Eonset = −0.03 V, E1/2 = −0.14 V) in alkaline electrolytes. Particularly, the catalyst possesses a significantly superior stability and immunity for methanol crossover and CO poisoning than that of Pt/C. The synthetic method is simple and cost-effective, providing a great opportunity to produce an eco-friendly and cheaper non-platinum fuel cell catalyst by using abundant natural biological resources.